1947-El escenario de la adhesión del principado de Cachemira a la Unión India - Travesedo de Castilla, Concepción (Cuadernos de Historia Contemporánea, 2006)
Most versions on the Indo-Pakistani conflict generated in 1947 by the accession of Jammu and Kashmir to India, draw alterations inherited from the propagandistic machinery of the Cold War. The assumption about the abuse of supremacy exerted by India, which would have deprived this Muslim territory from the Islamic nation of Pakistan, was not such. On the contrary, if the Kashmir population had been consulted in 1947, they would have opted for the incorporation to the democratic, socialist and secular India. The revision of the ethnic and political panorama in Kashmir, the examination of the legal dispositions established by the British to regulate the accession of the native States, and the analysis of the origins of the first India-Pakistan war in 1947, will temper, in this article, an historical version sculpted during the post World War period by the Western Powers to justify their support to the Pakistani ally.
Keywords: Kashmir; Transfer of Power in British India; Indo-Pakistani war of 1947-48; Interethnic affairs; Post World War Period